The interplay of landscape composition and configuration: new pathways to manage functional biodiversity and agroecosystem services across Europe. (7th April 2019) - Martin, Emily A.; Dainese, Matteo; Clough, Yann; Báldi, András; Bommarco, Riccardo; Gagic, Vesna; Garratt, Michael P.D.; Holzschuh, Andrea; Kleijn, David; Kovács‐Hostyánszki, Anikó; Marini, Lorenzo; Potts, Simon G.; et al.
Abstract: Managing agricultural landscapes to support biodiversity and ecosystem services is a key aim of a sustainable agriculture. However, how the spatial arrangement of crop fields and other habitats in landscapes impacts arthropods and their functions is poorly known. Synthesising data from 49 studies (1515 landscapes) across Europe, we examined effects of landscape composition (% habitats) and configuration (edge density) on arthropods in fields and their margins, pest control, pollination and yields. Configuration effects interacted with the proportions of crop and non‐crop habitats, and species' dietary, dispersal and overwintering traits led to contrasting responses to landscape variables. Overall, however, in landscapes with high edge density, 70% of pollinator and 44% of natural enemy species reached highest abundances and pollination and pest control improved 1.7‐ and 1.4‐fold respectively. Arable‐dominated landscapes with high edge densities achieved high yields. This suggests that enhancing edge density in European agroecosystems can promote functional biodiversity and yield‐enhancing ecosystem services.